Analysis of the Legal Basis of Marriage Agreements and Their Implications for the Position of Inheritance Property - Padma D. Liman; Aulia Rifai (Unissula, 2024)
This study explores the legal foundation of marriage agreements in Indonesia, specifically examining Law Number 1 of 1974 on Marriage and Constitutional Court Decision No. 69/PUU-XIII/2015. The primary focus of this research is to understand how marriage agreements impact the distribution of inheritance and their implications in resolving inheritance disputes. Meanwhile, Constitutional Court Decision No. 69/PUU-XIII/2015 expands the scope for creating and modifying marriage agreements during the marriage, providing additional flexibility that was previously unavailable. The methodology employed in this research is a normative juridical approach. A literature review method is used to gather relevant data and information from various legal sources. The primary legal materials used in this research include the Civil Code, Law Number 1 of 1974 on Marriage, and Constitutional Court Decision No. 69/PUU-XIII/2015. Additionally, secondary legal sources such as academic literature, legal journals, textbooks, and scientific articles are also utilized to enrich understanding and provide a broader theoretical context and perspective in the analysis. The findings indicate that a valid marriage agreement provides legal protection and certainty in the distribution of inheritance, while agreements not in accordance with positive law are at risk of being rejected in inheritance disputes.